A "Mah-Kinder" geopolitical explanation of China's Belt and Road Initiative (BRI). Issue 2 (4th March 2022) - Wey, Adam Leong Kok
Abstract: China's Belt and Road Initiative (BRI) has garnered a lot of attention, and worries about its impact and influence over Eurasia and Indo-Pacific. Two classical geopoliticians – Halford J. Mackinder and Alfred Thayer Mahan – had provided useful frameworks to explain China's BRI geopolitical implications, and geostrategies to dominate the Eurasian continent and Indo-Pacific waterways with economic tools and infrastructure projects. This article claims that China's BRI is a testament of the exceptional explanatory power of classical geopolitical theories in the practice of grand strategy in international politics.